Surrogate data: a novel approach to object detection - Tabor, Zbisław (Zielona Góra: Uniwersytet Zielonogórski)
In the present study a novel method is introduced to detect meaningful regions of a gray-level noisy images of binary structures. The method consists in generating surrogate data for an analyzed image. A surrogate image has the same (or almost the same) power spectrum and histogram of gray-level values as the original one but is random otherwise.
Keywords: surrogate data; optimal paths; fuzzy connectedness